Kerja Sama Perpustakaan IKOPIN dan Perpustakaan Universitas Al-Mas'oem dalam Memenuhi Kebutuhan Informasi Pengguna - Rukmana, Evi Nursanti; Rashifa, Saffana (Media Pustakawan, 2024)
IKOPIN and Al-Mas'oem University Libraries are university libraries that play an important role in supporting implementation of  Tri-Dharma of higher education. In order to fulfill this function, it is impossible for university libraries to act independently. Cooperation is needed in fulfillment, improvement, development, procurement and promotion of the services provided by the library to its users. This research aims to see how cooperation and impact of organizational structure in the cooperation carried out by IKOPIN Library and Al-Mas'oem University in meeting the information needs of users. This research has been conducted using a qualitative approach through a case study research instrument through observation, interviews, and literature studies. The process is carried out with the existence of MoA, MoU and discussions related to the collaboration. The impact of the cooperation between IKOPIN Library and Al-Mas'oem University can be seen in the improvement of quality and services that mainly affect users and librarians through cross borrowing services, librarian comparative studies, information exchange and joint collection procurement. In practice, the cooperation between the two libraries has not been successful. The unsuccessful cooperation between the two libraries is caused by many things, but the most likely is the inappropriate organizational structure implemented.